A Scoping Review of Care Trajectories across Multiple Settings for Persons with Dementia. Issue 1 (12th March 2022) - Kosteniuk, Julie G.; Morgan, Debra G.; Elliot, Valerie; Froehlich Chow, Amanda; Bayly, Melanie; Watson, Erin; Osman, Meric; Acan Osman, Beliz; O'Connell, Megan E.; Kirk, Andrew; Stewart, Norma; Cammer, Allison; et al.
Abstract: Multiple transitions across care settings can be disruptive for older adults with dementia and their care partners, and can lead to fragmented care with adverse outcomes. This scoping review was conducted to identify and classify care trajectories across multiple settings for people with dementia, and to understand the prevalence of multiple transitions and associated factors at the individual and organizational levels. Searches of three databases, limited to peer-reviewed studies published between 2007 and 2017, provided 33 articles for inclusion. We identified 26 distinct care trajectories. Common trajectories involved hospital readmission or discharge from hospital to long-term care. Factors associated with transitions were identified mainly at the level of demographic and medical characteristics. Findings suggest a need for investing in stronger community-based systems of care that may reduce transitions. Further research is recommended to address knowledge gaps about complex and longitudinal care trajectories and trajectories experienced by sub-populations of people living with dementia.